The Effect of Eight Weeks of Voluntary Wheel Running Exercise with Royal Jelly Consumption on Behavioral Disorders and Antioxidant Capacity in Rats with Trimethytin Model of Alzheimer's Disease - Maryam Azimpour; Mohammad Fathi; Omid Dezfoulian (Fasa University of Medical Sciences, 2021)
Background & Objective: Alzheimer is a neurodegenerative disease in which numerous changes occur in the patient's brain, since it is suggested that royal jelly (RJ) and Physical activity have several pharmacological activities, including neuroprotective and improvement of cognitive function. This study aimed to investigate the effect of eight weeks of voluntary wheel running exercise with royal jelly consumption on behavioral disorders and antioxidant capacity in rats with Trimethytin model of Alzheimer's disease. Materials & Methods: This experimental study was performed on 48 male rats; Alzheimer's Trimethytin was induced on 40 rats. The rats were then randomly divided into six groups each group consisting of 8 members: healthy control group (HC), Alzheimer control group (ADC), voluntary exercise (VW) (wheel running), sham (SH), voluntary exercise combined with the royal jelly intake (VWJ) and royal jelly intake (RJ). Voluntary wheel running was done for eight weeks, three sessions per week and 60 minutes each session. To determine depression and anxiety, The Forced Swimming Test (FST) and Elevated Plus-Maze (EPM) were used respectively. Real-Time PCR was used to determine Gene expression of Superoxide dismutase (SOD) and Glutathione peroxidase (GPX). Data analysis was performed by the multivariate analysis of variance (MANOVA) test and post hoc Scheffe at the significance level of P <0.05 using SPSS software version 20. Results: The results of multivariate analysis of variance show that there is a significant difference in all five variables of OAT, SOD, GPX, OAE and immobility in at least one group. According to the results of Scheffe post hoc test the findings showed that immobility time decreased in the VWJ, RJ, HC groups. The anxiety related indices increased in VWJ, RJ, HC groups. Although the differences in SOD antioxidant index were not significant, Gene expression of GPX increased in VWJ and RJ groups. Conclusion: In this study, voluntary exercise alone did not reduce anxiety and depression, and this highlights the role of Royal Jelly in it, and the results with the effect size of 0.757 showed the greatest effect on reducing the depression index. It seems that the combination of voluntary exercise with royal jelly supplementation can modulate behavioral disorders and antioxidant capacity in rats with trimethylettin-induced Alzheimer's disease.